Potential of AI in Simplifying Talent Acquisition in the IT Sector in India - Mangalampalli, Kavitha (Digital Repository of Theses - SSBM Geneva, 2024)
This study, explores the transformative role of artificial intelligence (AI) in modernizing recruitment processes within the Indian IT industry. The research addresses the inefficiencies inherent in traditional talent acquisition methods, such as manual resume screening and prolonged onboarding, which result in delays, increased costs, and reduced agility. The research focuses on understanding the impact of AI in improving the quality of the hires, role evolution of HR and time-saving aspects of automating such tasks. This paper adopted a quantitative research approach whereby data was collected through an online survey using structured questionnaires from the facilitators of HR in the IT sector in India. The findings reveal that AI significantly improves the quality of hires by facilitating better candidate assessments against top performers in similar roles. Additionally, AI-driven processes are shown to impact HR roles, shifting the focus towards more strategic functions, while automation streamlines administrative tasks, leading to increased efficiency. The study concludes that AI has immense potential to revolutionize talent acquisition in the Indian IT sector, providing both opportunities and challenges. Ethical considerations, particularly regarding bias and fairness, are highlighted as critical areas for ongoing attention. The study provides insightful information for IT companies wishing to use AI to improve their hiring procedures, which would ultimately lead to more efficient, effective, and fair hiring procedures. It is advised that future studies examine the long-term effects of AI-driven hiring and go deeper into ethical issues.